2014
DOI: 10.15296/ijwhr.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on Post-Partum Severe Acute Maternal Morbidity And Maternal Deaths in A Tertiary Level Teaching Hospital of Eastern India

Abstract: Objectives: Identification of severe acute maternal morbidity (SAMM) has gained importance in recent years in view of falling maternal death rates and thrust on improving quality of maternal health care. Although most of these events occur in developing countries, reporting system for SAMM is poorly developed in these regions. Aim of this study was to determine the incidence and direct causes of postpartum SAMM along with measuring of relevant new indicators on maternal health in an apex institute of India Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…It was found to be lower than other studies which indicate the requirement of better referral services at our centers. [41314] In some studies, MNM ratio was found to be lower than the present study. [31516]…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…It was found to be lower than other studies which indicate the requirement of better referral services at our centers. [41314] In some studies, MNM ratio was found to be lower than the present study. [31516]…”
Section: Discussioncontrasting
confidence: 58%
“…In the present study, near miss: death ratio was found somewhat similar to other studies,[51417] while in some other states, it was found to be higher. [41316] Higher near miss mortality ratio indicates a better quality of care at that facility. The present study has been done in a tertiary referral center covering most districts in and around Ahmedabad, with most of the cases being referred in an already moribund state, leading to less near miss and more of MD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,14,15 While in some other states, it was found to be higher. 7,16,17 Higher near miss : Mortality ratio indicate a better quality of care at that facility. Critical care facility in Chattogram Maa-O-Shishu Hospital (CMOSH) still needs further improvement.…”
Section: Groupingmentioning
confidence: 99%